Effect of Heavy Metal Contaminated Waste Water Irrigation on Enzymatic and Non Enzymatic Antioxidants in Some Selected Vegetables. (May 2020) - Singh, Jagdev; Mohan, Dr Anand
Abstract: The study was conducted to investigate the bioaccumulation of heavy metals (As, Cd, Cr and Pb) and their effect on the antioxidant level and activity in vegetables Raphanus sativus, Spinacea oleracea, Brassica oleracea and Lycopersicum esculentum irrigated with heavy metal loaded waste water of Buddha Nullah. The results of the study revealed bioaccumulation of heavy metals in vegetables and the level of non-enzymatic antioxidants, ascorbic acid and proline and enzymatic antioxidants, catalase and peroxidase was found to be much higher in waste water irrigated vegetables in comarison to the level of bioaccumulation of heavy metals as well as antioxidants in same vegetables irrigated with normal borewell water as control. This indicates that heavy metals induce oxidative stress (ROS) in the plants at cellular level and to nullify the toxic effect these heavy metals the cell mechanism increase the production and activity of both non-enzymatic and enzymatic antioxidants.